Colostrum-Driven Epigenetic Programming in Dairy Cows: A Pathway to Optimal Reproductive Health - Md. Emran Hossain (Emerging Trends in Metabolites, 2025)
Colostrum is a vital nutritional source for neonatal calves, providing immune support and essential growth factors. Recent research suggests that colostrum’s impact extends beyond immediate immunological protection, influencing long-term reproductive health through epigenetic modifications. In dairy heifers, early-life exposure to high-quality colostrum may program the developing reproductive system, affecting ovarian function, uterine health, and overall fertility. The components of colostrum, including hormones, growth factors, and bioactive peptides, can induce epigenetic changes that can alter gene expression patterns involved in reproductive tissue development and hormonal regulation. These modifications can potentially enhance reproductive efficiency by optimizing ovarian reserve, improving follicular development, and promoting uterine health. This review explores the mechanisms through which colostrum-driven epigenetic programming influences the reproductive health of dairy heifers. It highlights the critical role of colostrum in regulating genes associated with puberty onset, ovarian function, and reproductive longevity. Moreover, it examines the interaction between colostrum nutrients and the gut-reproductive axis, shedding light on how early gut health impacts hormonal pathways governing reproduction. Understanding these processes could provide new strategies for improving fertility and productivity in dairy herds. By optimizing colostrum management practices, it may be possible to enhance reproductive outcomes, ensuring sustainable dairy farming practices and long-term herd performance.
Keywords: colostrum; dairy heifers; endocrine regulation; epigenetic programming; fertility; immune modulation; ovarian function; puberty onset